2019
DOI: 10.1109/access.2019.2936419
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Approach to Risk-Based Maintenance Scheduling for HV Cables

Abstract: Regular maintenance inspection and testing is essential in extending cable life and reducing failure probability. This can be achieved by improving the conduit conditions and taking corrective actions on faulty cable components and accessories. Regulators and corporate governance among power utilities require the implementation of risk-based approaches to asset management. However, practitioners lack sufficient historical event data and knowledge that allow them to determine the failure probability of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…To build the vector, the values of CDF, PDF, reliability, failure rate and availability are calculated at 1000 operating hours and the shape parameter is taken to be 1. Table 6 presents the values of each of the parameters [31]. 7 shows the priority or preference table which is a vector.…”
Section: Priority Vector For Equipment Selectionmentioning
confidence: 99%
“…To build the vector, the values of CDF, PDF, reliability, failure rate and availability are calculated at 1000 operating hours and the shape parameter is taken to be 1. Table 6 presents the values of each of the parameters [31]. 7 shows the priority or preference table which is a vector.…”
Section: Priority Vector For Equipment Selectionmentioning
confidence: 99%
“…Here the model of estimated failure number with consideration of time delay is compared with the model without. According to the previous work of the present authors [22], the model ignoring the time delay is shown in (15): mhT=)(1β][1)(1βY/TkTβ m hT is the expected cumulative number of failures in 1 year according to the model without considering time delay. β is also noted as the rate of defects that can be detected through inspection.…”
Section: Time‐delay‐based Cable Failure Modellingmentioning
confidence: 99%
“…An approach to maintenance scheduling of HV cable system needs to consider the following two factors: (i) A cable system failure event may be caused (triggered) by the failure of an individual component. From a practitioner's perspective, cable circuits can be divided into cable conduit, cable terminations, joints, main bodies and earthing systems, for this facilitates inspections and testing. (ii) On the other hand, a failure may occur at any time instant of its life cycle, depending on its causes and operational stresses [22]. It is known that failure rate curves over the life cycle of most equipment are bathtub shaped.…”
Section: Maintenance Scheduling Based On Time‐delay Failure Modelmentioning
confidence: 99%
“…In the modern electrical industry, engineers and specialist technicians are responsible for maintaining and operating the electrical equipment, cables, and machines that integrate the electrical systems of substations or power plants [1]. Extending the useful life of these assets by lessening the sources that may cause deterioration or possible failures is a fundamental part of the work such specialists must perform [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In the modern electrical industry, engineers and specialist technicians are responsible for maintaining and operating the electrical equipment, cables, and machines that integrate the electrical systems of substations or power plants [1]. Extending the useful life of these assets by lessening the sources that may cause deterioration or possible failures is a fundamental part of the work such specialists must perform [1][2][3][4]. Regarding high voltage electrical assets, it is well known that a big part of the failures usually occurs in the insulation system, due to the uncontrolled presence of multiple ageing mechanisms of electrical, mechanical, thermal, and environmental origin [2,3,[5][6][7], which, over time, tend to accelerate the loss of the dielectric properties of the material, leading to the anticipated failure of the equipment.…”
Section: Introductionmentioning
confidence: 99%